Sulfur autotrophic denitrification filler and preparation method thereof

By adopting sulfur autotrophic denitrification fillers with specific formulas and preparation methods, the problems of low sulfur source utilization efficiency and poor microbial mass transfer effect in existing fillers are solved, and efficient, economical and environmentally friendly sewage treatment effect is achieved.

CN118702276BActive Publication Date: 2025-04-15SHENZHEN ZHENDING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411005021.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-15
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The existing sulfur autotrophic denitrification fillers have problems such as low sulfur source utilization efficiency, poor microbial mass transfer effect, high filler cost, and high application difficulty, resulting in limited promotion in the fields of sewage treatment and water environment governance.

Method used

A sulfur autotrophic denitrification filler including ferric chloride, calcium chloride, polyacrylamide, calcium phosphate, huriacic acid, starch, sulfur powder, pyrote powder and baking soda powder is used to improve the denitrification efficiency of microorganisms and the economic and environmental friendliness of the filler through specific formulas and preparation methods.

Benefits of technology

It has achieved rapid in-situ domestication of sulfur autotrophic denitrifying bacteria, improved nitrogen removal efficiency, reduced filler costs, enhanced environmental friendliness, and was suitable for areas such as sewage treatment and water environment governance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118702276B_ABST
    Figure CN118702276B_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur autotrophic denitrification filler and a preparation method thereof. A sulfur autotrophic denitrification filler, the sulfur autotrophic denitrification filler comprises the following preparation raw materials: ferric chloride, calcium chloride, polyacrylamide, calcium phosphate, humic acid, starch, sulfur powder, pyrite powder, baking soda and water. The sulfur autotrophic denitrification filler of the invention not only has the ability to quickly domesticate sulfur autotrophic denitrifying bacteria in situ, but also shows good economy and environmental friendliness in practical applications. The filler has broad application prospects and potential market value in the fields of sewage treatment, water environment management, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of environmental functional materials and sewage denitrification treatment, and in particular to a sulfur autotrophic denitrification filler and a preparation method thereof. Background Art

[0002] The current biological denitrification technologies for sewage denitrification mainly include traditional full-process heterotrophic denitrification technology, short-term denitrification coupled anaerobic ammonium oxidation technology, short-term nitrification coupled anaerobic ammonium oxidation technology, hydrogen autotrophic denitrification technology and sulfur autotrophic denitrification technology. The above technical classifications are mainly distinguished by the reaction matrix. Traditional heterotrophic denitrification technology is that microorganisms use organic matter as electron donors and nitrite or nitrate as electron acceptors for denitrification, while anaerobic ammonium oxidation technology mainly controls the ratio of ammonia nitrogen and nitrite nitrogen in the front-end water to denitrify under the action of anaerobic ammonium oxidation bacteria, and hydrogen autotrophic denitrification uses hydrogen as an electron donor and nitrite or nitrate as an electron acceptor for denitrification. Finally, sulfur autotrophic denitrification uses one or more sulfur sources as electron donors and nitrite and nitrate as electron acceptors for denitrification.

[0003] Although most new denitrification processes have shown that they can save operating costs, there are still key issues that make it difficult to promote them. For example, anaerobic ammonia oxidation technology has a strict ratio of ammonia nitrogen to nitrite nitrogen, and the acclimatization speed is slow. It has high requirements for water quality and environment. It often requires senior technical personnel to debug and a large amount of sludge cost investment in the early stage before it can be effective. Not only that, about 10% of the total nitrogen mass removed by anaerobic ammonia oxidation will be converted into nitrate nitrogen, which still requires a back-end process to treat nitrate nitrogen to meet emission requirements. Therefore, the engineering application of anaerobic ammonia oxidation, especially in high-ammonia nitrogen wastewater, is difficult, with high initial investment costs and high maintenance difficulties in the later stage. Hydrogen autotrophic denitrification technology is a recent research hotspot, but it is not yet mature, and there are certain safety hazards in the application scenarios. When the professional quality of technicians and operators is not high, safety accidents may occur, and the construction, installation or modification costs of the reactor are extremely high, and the operating cost reduction is not obvious, which hinders promotion.

[0004] Sulfur autotrophic denitrification is a process that uses sulfur sources for denitrification. Generally speaking, the water inlet mode of a sewage treatment plant is continuous flow water inlet, which has great restrictions on the types of sulfur sources used. When choosing to use a water-soluble sulfur source, on the one hand, the efficient utilization of microorganisms requires a certain sulfur source concentration, and on the other hand, continuous flow water inlet will lead to the loss of a large amount of sulfur sources. The lost sulfur source may cause the effluent to have an unpleasant odor and sludge sedimentation difficulties when it comes to the back-end process. At present, the sulfur autotrophic denitrification process uses more solid sulfur sources, such as elemental sulfur and pyrite. There are many sulfur autotrophic fillers on the market, but these fillers still have some problems, such as the combination of pyrite and sulfur. Generally speaking, the ratio of pyrite to sulfur is greater than 1:5, but the actual microbial metabolic rates of pyrite and sulfur are very different. Pyrite was originally used as an auxiliary material to enhance the electron mass transfer effect and thus improve the denitrification activity of microorganisms. In the later stage, it became a discarded bottom mud that is difficult to discharge at the bottom of the reactor. In addition, many sulfur autotrophic fillers cannot achieve true sustained release. The adhesives used in many fillers generally have problems such as long metabolism time, stable chemical substances, and too fast dissolution rate, which limits the denitrification effect of the filler. There are also mass transfer problems when using polyvinyl alcohol or sodium alginate to make embedded sulfur autotrophic fillers. Since materials such as sulfur or pyrite are insoluble in water, and the embedding materials have certain chemical stability, it is difficult to cultivate sulfur autotrophic bacteria. When sulfur autotrophic bacteria are directly embedded in the material, the required sulfur autotrophic bacteria are large in scale, and the sulfur autotrophic bacteria are not other heterotrophic bacteria. They cannot effectively degrade large molecular organic matter, and the sulfur source mass transfer effect is extremely poor, which easily leads to the sulfur autotrophic bacteria eventually entering a state of starvation. When elemental sulfur is used as a sulfur source, it is often not used as a filler alone. Its efficiency is low, and sulfur may be discharged with water in the effluent, resulting in SS exceeding the standard. In terms of price cost, the existing commercially available sulfur autotrophic fillers are too expensive, which brings great resistance to the implementation and promotion of technology.

[0005] Therefore, in order to solve the above problems, the present invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. Summary of the invention

[0006] In view of the shortcomings of current sulfur autotrophic denitrification fillers, the present invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. The sulfur autotrophic denitrification filler of the present invention not only has the ability to quickly domesticate sulfur autotrophic denitrifying bacteria in situ, but also shows good economy and environmental friendliness in practical applications. The filler has broad application prospects and potential market value in the fields of sewage treatment, water environment management, etc.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a sulfur autotrophic denitrification filler, which comprises the following preparation raw materials: ferric chloride, calcium chloride, polyacrylamide, calcium phosphate, humic acid, starch, sulfur powder, pyrite powder, baking soda and water.

[0009] Preferably, the sulfur autotrophic denitrification filler comprises the following raw materials in parts by weight: 1-2 parts of ferric chloride, 0.4-0.6 parts of calcium chloride, 0.4-0.6 parts of polyacrylamide, 1-2 parts of calcium phosphate, 1-2 parts of humic acid, 10-20 parts of starch, 80-120 parts of sulfur powder, 4-8 parts of pyrite powder, and 1-4 parts of baking soda.

[0010] Further preferably, the mass ratio of the sulfur powder, pyrite powder and baking soda powder is (40-50):(1-3):1.

[0011] Preferably, the particle size of the sulfur powder is greater than 200 mesh, and the particle size of the pyrite powder is greater than 200 mesh.

[0012] The second aspect of the present invention provides a method for preparing the sulfur autotrophic denitrification filler, comprising the following steps:

[0013] (1) mixing water, ferric chloride, calcium chloride, polyacrylamide, calcium phosphate and humic acid, heating and stirring to obtain a pre-filling mixed solution;

[0014] (2) adding starch to the pre-filling mixed solution, heating and stirring to gelatinize the starch, adding water, stirring and cooling to obtain a filler adhesive;

[0015] (3) mixing the filler binder with sulfur powder, pyrite powder and baking soda to obtain a filler mixed wet material;

[0016] (4) adding the filler mixed wet material into a mold, and then heating it, and cooling it to room temperature after heating, so as to obtain the sulfur autotrophic denitrification filler.

[0017] Preferably, in step (1), the temperature of the heating and stirring is 60-70°C.

[0018] Preferably, in step (2), the heating and stirring time is ≥ 20 min.

[0019] Preferably, in step (3), the sulfur powder, pyrite powder and baking soda are first mixed to prepare a mixed dry material, and then the mixed dry material is mixed with the filler adhesive; the mass ratio of the filler adhesive to the mixed dry material is 1:(1.5-2.5).

[0020] Further preferably, in step (3), the temperature of the mixture is maintained at ≥ 60°C during the mixing process.

[0021] Preferably, in step (4), the heating step is to first control the temperature to 50-60°C, maintain it for 5-30 minutes, then adjust the temperature to 65-75°C, and continue constant temperature heating for 5-20 minutes.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. Ferric chloride is added to the mixed solution before preparing the filler, and the ferric chloride is dissolved in water to become an ion exchange state that is more suitable for being utilized by microorganisms. Compared with pyrite, the activity of the iron ions is higher. At the same time, the presence of other ions and humic acid controls the ion activity, thereby achieving full utilization of the iron ions, improving the denitrification efficiency of the microorganisms, ensuring the inorganic salt concentration in the solution, and avoiding the waste of iron-containing raw materials.

[0024] The invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. Calcium chloride is added when preparing a pre-mixed liquid for fillers. The calcium chloride dissolves quickly and can be dispersed in the pre-mixed liquid by means of rapid stirring. After drying, a certain hardness can be added to the filler to prevent the supported filler from being easily broken or lost.

[0025] The invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. Polyacrylamide is added when preparing a pre-filler mixed solution, which can provide a certain viscosity of the pre-mixed solution, so that the added poorly soluble or insoluble substances are dispersed more evenly, are not easy to lose, and do not sink to the bottom, and also prepare for the subsequent addition of dry materials.

[0026] The invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. Calcium phosphate is added when preparing a pre-filler mixed solution. Calcium phosphate is used as an anti-caking agent and a slow-release phosphorus supplementer. It is a slightly soluble agent in water and can prevent dry materials from agglomerating. The slowly released phosphate can be used by microorganisms to improve the ability to remove pollutants.

[0027] The present invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material, in which humic acid is added when preparing the mixed solution before the filler. Unlike other technologies, the addition of humic acid can accelerate the growth and reproduction of microorganisms. Humic acid, as a microbial nutrient element slow-release agent, has a colloid-like property in water, contains a variety of active functional groups, can be used as a miniature ion exchange bed, is suitable for the growth and reproduction of microorganisms, and initially a part of it will be fixed under the action of calcium and iron ions, and the solubility is relatively low. When the filler is put into water for use after being manufactured, the fixed humic acid can be reactivated due to the presence of monovalent cations such as potassium and sodium contained in the wastewater, so that it can be fully utilized by the microorganisms.

[0028] The present invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material, in which starch is added when making a filler adhesive. The starch can not only be gelatinized at a suitable temperature to form an adhesive with a high viscosity, but can also be used by microorganisms as a polysaccharide biomass. Unlike others, starch cannot be used directly for microbial denitrification. It needs to undergo multiple degradation reactions of multiple microorganisms to form small-molecule organic acids or small-molecule sugars before it can be used by microorganisms for denitrification. Small-molecule organic matter quickly dissolves in water, so when starch is used as an adhesive, the microorganisms it brings will not cause fierce niche competition with sulfur autotrophic denitrification microorganisms. After starch is gelatinized and then dried, the physical properties of the starch paste with poor water solubility are relatively stable at low temperatures, but after the decomposition of microorganisms, the starch will be gradually decomposed, so that the nutrients wrapped therein are released, achieving a real slow-release effect. In addition, the small-molecule organic matter decomposed by starch can also be used as an organic carbon source for denitrification, further improving the denitrification activity, and is the material basis for synchronous autotrophic denitrification and heterotrophic denitrification.

[0029] The invention provides a highly efficient and clean sulfur autotrophic biological slow-release filter material. When dry powder is added, in addition to the main sulfur, a small amount of pyrite is also added, and the proportion is appropriate, so that too much pyrite will not be wasted due to sedimentation. In addition, the added baking soda has a certain pore-forming effect on filler preparation, and the baking soda can also provide alkalinity. After decomposition, each 1 mol of baking soda can be hydrolyzed to produce 1 mol of hydroxide ions. The sulfur autotrophic denitrifying bacteria is a microorganism with a relatively large alkali consumption, so the alkalinity needs to be supplemented in the denitrification process, and the addition of baking soda can relieve part of the alkalinity pressure, so that the filler is more suitable for microbial growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a comparison diagram of the denitrification effects of different sulfur autotrophic reactors started up in Example 4;

[0031] Figure 2 This is a comparison diagram of denitrification effects of different sulfur autotrophic reactors with high influent total nitrogen load in Example 5;

[0032] Figure 3 This is a comparison diagram of denitrification effects of different sulfur autotrophic reactors when treating electroplating wastewater in Example 6;

[0033] Figure 4 The community distribution characteristics at the reactor 1 level;

[0034] Figure 5 These are the genus-level community distribution characteristics of reactor 1. DETAILED DESCRIPTION

[0035] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0037] Example 1

[0038] (1) 750 mL of clean water was placed in a 1000 mL constant temperature stirring device, the constant temperature was set to 70° C., the stirrer and the heater were turned on, and then 5 g of polyacrylamide was added and stirred for 5 minutes. Then 20 g of ferric chloride powder, 5 g of calcium chloride powder, 20 g of calcium phosphate and 20 g of humic acid were added to the constant temperature stirring device and stirred for 5 minutes to obtain a pre-filling mixed solution.

[0039] (2) At a constant temperature of 70°C, 100 g of starch was slowly added to the pre-filling mixed solution while stirring to fully gelatinize the starch. After the addition was completed and stirring was continued for 10 minutes, 100 mL of clean water was added and stirring was continued for 20 minutes to obtain a filler adhesive.

[0040] (3) Take 500 g of sulfur powder and put it into a hand-cranked jar, then take 30 g of pyrite powder and 10 g of baking soda and add them into the hand-cranked jar, and then shake it thoroughly to obtain a mixed dry material.

[0041] (4) While hot, the filler binder and the mixed dry material are mixed in a ratio of 20:40, and the mixing method is to add slowly and keep the temperature above 60° C. After mixing, continue to stir vigorously for 5 minutes to obtain a mixed filler blank 1.

[0042] (5) Add the mixed filler blank 1 into the mold, control the heating temperature at 55° C., maintain for 10 minutes, then adjust the temperature to 70° C., maintain for 10 minutes, finally stop heating, cool to room temperature, and package for storage, thereby obtaining an efficient and clean sulfur autotrophic biological slow-release filter material 1.

[0043] Example 2

[0044] (1) Take 750 mL of clean water and put it into a 1000 mL constant temperature stirring device, set the constant temperature to 70°C, turn on the stirrer and the heater, then take 5 g of polyacrylamide and stir it thoroughly for 5 minutes, then take 20 g of ferric chloride powder and 5 g of calcium chloride powder and add them into the constant temperature stirring device, stir it thoroughly for 5 minutes to prepare a pre-filling mixed solution.

[0045] (2) At a constant temperature of 70°C, 100 g of starch was slowly added to the pre-filling mixed solution while stirring to fully gelatinize the starch. After the addition was completed and stirring was continued for 10 minutes, 100 mL of clean water was added and stirring was continued for 20 minutes to obtain a filler adhesive.

[0046] (3) Take 500 g of sulfur powder and put it into a hand-cranked jar, then take 30 g of pyrite powder and 10 g of baking soda and add them into the hand-cranked jar, and then shake it thoroughly to obtain a mixed dry material.

[0047] (4) While hot, the filler binder and the mixed dry material are mixed in a ratio of 20:40, and the mixing method is to add slowly and keep the temperature above 60° C. After mixing, continue to stir vigorously for 5 minutes to obtain a mixed filler blank 2.

[0048] (5) Add the mixed filler blank 2 into the mold, control the heating temperature at 55°C, maintain for 10 minutes, then adjust the temperature to 70°C, maintain for 10 minutes, finally stop heating, cool to room temperature, and package for storage, thereby obtaining a biological slow-release filter material 2.

[0049] Example 3

[0050] (1) Take 750 mL of clean water and put it into a 1000 mL constant temperature stirring device, set the constant temperature to 70°C, turn on the stirrer and the heater, then take 5 g of polyacrylamide and stir it thoroughly for 5 minutes, then take 20 g of calcium phosphate and 20 g of humic acid and add them into the constant temperature stirring device, stir it thoroughly for 5 minutes, and prepare a pre-filling mixed solution.

[0051] (2) At a constant temperature of 70°C, 100 g of starch was slowly added to the pre-filling mixed solution while stirring to fully gelatinize the starch. After the addition was completed and stirring was continued for 10 minutes, 100 mL of clean water was added and stirring was continued for 20 minutes to obtain a filler adhesive.

[0052] (3) Take 500 g of sulfur powder and put it into a hand-cranked jar, then take 30 g of pyrite powder and 10 g of baking soda and add them into the hand-cranked jar, and then shake it thoroughly to obtain a mixed dry material.

[0053] (4) While hot, the filler binder and the mixed dry material are mixed in a ratio of 20:40, and the mixing method is to add slowly and keep the temperature above 60° C. After mixing, continue to stir vigorously for 5 minutes to obtain a mixed filler blank 3.

[0054] (5) Add the mixed filler blank 3 into the mold, control the heating temperature at 55°C, maintain for 10 minutes, then adjust the temperature to 70°C, maintain for 10 minutes, finally stop heating, cool to room temperature, and package for storage, thereby obtaining a biological slow-release filter material 3.

[0055] Example 4

[0056] (1) 300 g of a highly efficient and clean sulfur autotrophic biological slow-release filter material 1 in Example 1 was placed in a 1 L column reactor 1, and 300 g of biological slow-release filter materials 2 and 3 in Example 3 were placed in 1 L column reactor 2 and 1 L column reactor 3, respectively. 300 g of pure sulfur blocks with a particle size of about 3 cm were placed in a reactor 4. The reactor was a spliced ​​three-section structure, and the filter material was sandwiched in the middle of the reactor by a porous flange plate, with internal reflux devices at the top and bottom.

[0057] (2) Simultaneously add self-configured biochemical influent to reactor 1, reactor 2, reactor 3 and reactor 4. In addition to the necessary biochemical nutrients, the influent ammonia nitrogen concentration is 10 mg / L, the influent nitrite nitrogen is 0 mg / L, the influent nitrate nitrogen is 500 mg / L, the influent COD is 40 mg / L, pH=8, the phosphate concentration is 2 mg / L, the hydraulic retention time is 24 hours, and the sludge from the municipal sewage plant is used as the initial seed sludge for domestication at a sludge concentration of 3000 mg / L MLVSS. At the same time, internal recirculation is designed, and the daily recirculation water volume is 6 L / d. The nitrate nitrogen in the three reactors is measured every two days. After 60 days of operation, the results are as shown in the attached figure. Figure 1 shown.

[0058] Example 5

[0059] The four reactors after the experiment of Example 4 were taken to continue the experiment. The experimental parameters were adjusted to a hydraulic retention time of 12 hours, that is, the total nitrogen load of the influent was doubled. Self-configured biochemical influent was added to reactors 1, 2, 3 and 4. In addition to the necessary biochemical nutrients, the influent ammonia nitrogen concentration was 10 mg / L, the influent nitrite nitrogen was 0 mg / L, the influent nitrate nitrogen was 500 mg / L, the influent COD was 40 mg / L, pH = 8, the phosphate concentration was 2 mg / L, and the hydraulic retention time was 12 hours. It was run for 30 days.

[0060] The experimental results are as attached Figure 2 As shown, it is verified that under high load conditions, the filler of the present invention has a significant denitrification advantage.

[0061] Example 6

[0062] The reactor in Example 5 was used to continue the test, only the test water was changed, and the rest remained unchanged. The inlet water was changed to electroplating tin-stripping wastewater (take electroplating comprehensive water and dilute it 200 times), and after physical and chemical treatment to remove biological toxicity, its pH was 8.0-9.5, the nitrate nitrogen concentration was 500-600 mg / L, the ammonia nitrogen concentration was 1.5 mg / L, and the total phosphorus concentration was controlled to 1 mg / L by adding potassium dihydrogen phosphate.

[0063] The nitric nitrogen in the four reactors was measured every day. After 60 days of operation, the results are shown in the attached figure. Figure 3 shown.

[0064] Example 7

[0065] High-throughput sequencing was performed on the biochemical sludge in reactor 1 of Examples 4 and 5 to determine the characteristics of the microbial community at 0 days, 60 days and 90 days. The results are shown in the attached Figure 4 and 5 .

[0066] Attached Figure 4 The results showed that the main bacterial phyla of the initial sludge were Proteobacteria, Bacteroidota, Firmicutes and Deinococcota. After the biological acclimation reaction, Campylobacterota began to appear, and its relative abundance in reactor 1 was 47.61% and 58.95% on the 60th and 90th days, respectively. Campylobacterota is related to sulfur autotrophic denitrifiers, indicating that sulfur autotrophic denitrifiers show advantages under the acclimation of sulfur autotrophic denitrification filler 1, and the filler of reactor 1 has excellent sulfur autotrophic microbial affinity. At the same time, the relative abundance of Firmicutes decreased, which may be due to the low C / N ratio and the microbial selectivity on the surface of sulfur autotrophic biological filler 1.

[0067] Attached Figure 5 The results show that the main microbial genera in reactor 1 are Sulfurimonas, Limnobacter, Lentimicrobium, Sporosarcina, Truepera and Tissierella. Sulfurimonas is a significantly dominant genus, and its relative abundance increased from undetected to 43.96% on the 60th day, and continued to increase. The significant dominance of Sulfurimonas indicates that the filler used in reactor 1 has the ability to quickly start efficient sulfur autotrophic denitrification in situ.

[0068] The results show that the sulfur autotrophic denitrification filler of the present invention can quickly domesticate sulfur autotrophic denitrifying bacteria in situ, and can be used continuously for at least 90 days, and its related bacteria show an upward advantage, which is consistent with the denitrification ability performance. In addition, by comparing the changes in the microbial community structure at different time points (0 days, 60 days and 90 days), the growth and succession process of sulfur autotrophic denitrifying bacteria in the reactor can be further understood. As the reaction proceeds, not only the relative abundance of sulfur autotrophic denitrifying bacteria such as Sulfomonas increases significantly, but other microorganisms related to the sulfur cycle may also be promoted or inhibited, thereby jointly forming a complex microbial ecosystem.

[0069] Finally, the sulfur autotrophic denitrification filler of the present invention not only has the ability to quickly domesticate sulfur autotrophic denitrifying bacteria in situ, but also shows good economy and environmental friendliness in practical applications. Therefore, the filler has broad application prospects and potential market value in the fields of sewage treatment, water environment management, etc.

[0070] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A sulfur autotrophic denitrification filler, characterized in that: The sulfur autotrophic denitrification filler comprises the following raw materials in parts by weight: 1-2 parts of ferric chloride, 0.4-0.6 parts of calcium chloride, 0.4-0.6 parts of polyacrylamide, 1-2 parts of calcium phosphate, 1-2 parts of humic acid, 10-20 parts of starch, 80-120 parts of sulfur powder, 4-8 parts of pyrite powder, and 1-4 parts of baking soda; The preparation method of the sulfur autotrophic denitrification filler comprises the following steps: (1) mixing water, ferric chloride, calcium chloride, polyacrylamide, calcium phosphate and humic acid, heating and stirring to obtain a pre-filling mixed solution; (2) adding starch to the pre-filling mixed solution, heating and stirring to gelatinize the starch, adding water, stirring and cooling to obtain a filler adhesive; (3) mixing the filler binder with sulfur powder, pyrite powder and baking soda to obtain a filler mixed wet material; (4) adding the filler mixed wet material into a mold, and then heating it, and cooling it to room temperature after heating, so as to obtain the sulfur autotrophic denitrification filler.

2. The sulfur autotrophic denitrification filler according to claim 1, characterized in that: The mass ratio of the sulfur powder, pyrite powder and baking soda powder is (40-50):(1-3):

1.

3. The sulfur autotrophic denitrification filler according to claim 1, characterized in that: The particle size of the sulfur powder is greater than 200 mesh, and the particle size of the pyrite powder is greater than 200 mesh.

4. The method for preparing the sulfur autotrophic denitrification filler according to claim 1, characterized in that: In step (1), the temperature of the heating and stirring is 60-70°C.

5. The method for preparing the sulfur autotrophic denitrification filler according to claim 1, characterized in that: In step (2), the heating and stirring time is ≥ 20 min.

6. The method for preparing the sulfur autotrophic denitrification filler according to claim 1, characterized in that: In step (3), the sulfur powder, pyrite powder and baking soda are first mixed to prepare a mixed dry material, and then the mixed dry material is mixed with the filler adhesive; the mass ratio of the filler adhesive to the mixed dry material is 1:(1.5-2.5).

7. The method for preparing the sulfur autotrophic denitrification filler according to claim 1, characterized in that: During the mixing process, the temperature of the mixed material is maintained at ≥ 60°C.

8. The method for preparing the sulfur autotrophic denitrification filler according to claim 1, characterized in that: In step (4), the heating step is to first control the temperature to 50-60°C, maintain it for 5-30 minutes, then adjust the temperature to 65-75°C, and continue to heat at the constant temperature for 5-20 minutes.

Citation Information

Patent Citations

  • Method for promoting anaerobic ammonia oxygen microbiological activity at normal and low temperatures, anaerobic ammonia oxidation promoter and application of method

    CN112694168A

  • Sewage treatment agent, autotrophic denitrification microbial carrier and preparation method of autotrophic denitrification microbial carrier

    CN112978912A

  • Biofilm carrier material and preparation method thereof

    CN116037080A

  • Lightweight and reusable sulfur autotrophic denitrification filler and preparation method thereof

    CN118062991A